2017
DOI: 10.4314/ahs.v16i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of utilization of ante-natal and delivery services in a semi-urban community of North-Central Nigeria

Abstract: Abstract:Background: Nigeria accounts for only 2% of the world's population, but contributes up to 10 % of the global estimates of maternal deaths. The study assesses the utilization of antenatal and delivery services by women of reproductive age in Afon community. Methodology: It was a descriptive cross-sectional study that collected both quantitative and qualitative data using semi-structured interviewer administered questionnaire and focus group discussions (FGD). Interviews were house-hold based. FGD had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 13 publications
4
39
0
1
Order By: Relevance
“…This finding is in agreement with other studies done in Africa [27,28]. Messages could be well designed to focus on the impact of the disease on the infant, to increase likelihood of vaccination [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with other studies done in Africa [27,28]. Messages could be well designed to focus on the impact of the disease on the infant, to increase likelihood of vaccination [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…We found that some women do not start ANC early because they demand new clothes from their husbands. This was also reported in other studies done in South Africa and Nigeria where women were reported to start ANC late because they needed to find money for transport and new clothes [ 19 , 20 ]. The finding of the studies shows that socio-economic status may be associated with the decision to seek health services especially on time to start ANC.…”
Section: Discussionsupporting
confidence: 74%
“…[41] "I cannot go to the health facility for care during pregnancy because am not sick". [42 P.969] "Some people believe is only God that can help to deliver and so prefer to stay back at home for delivery, besides it is very comfortable and at no cost" [42] "Yes, attending for ANC is important but you only go there to deliver if you become weak or cannot deliver on your own without assistance . .…”
Section: Data Extraction and Meta-synthesismentioning
confidence: 99%
“…. One goes there only if a problem develops or when the labour takes much time" [39] "Some women prefer traditional home because if there is difficulty during delivery, spiritual intervention can be obtained" [42] "Allah (God) has now brought succor in ANC. Labor is now short, quick and uncomplicated.…”
Section: Data Extraction and Meta-synthesismentioning
confidence: 99%
See 1 more Smart Citation